Elimination of maternal antibodies against measles (Is the policy of vaccinating children younger than nine months of age suitable for Turkey?) - Kanra, Güler; Ceyhan, Mehmet (The Turkish Journal of Pediatrics, 1991)
Maternal antibodies against measles in 223 healthy children aged 22 to 31 weeks were studied. The ratio of children with detectable antibodies declined from 61.4 percent at 22-23 weeks of age to 20 percent at 26-27 weeks of age. Since the minimum proportion of antibody-positive children (15.6% at 26-27 weeks of age) is still higher than the optimum proportion (5%), the Schwarz vaccine which is used mostly in measles immunization seems not to be effective to obtain a high seroconversion rate in our infants. We suggest that the Edmonston-Zagreb strain of measles vaccine be used for infants under 9 months of age in Turkey.
Keywords: maternal antibodies against measles; measles vaccination